2018
DOI: 10.1055/s-0037-1609581
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Catalytic Atroposelective Synthesis of Diaryl Ethers Through C(sp2)–H Alkylation with Nitroalkanes

Abstract: Herein we report studies towards a small molecule catalytic approach to access atropisomeric diaryl ethers that proceeds via a C(sp2)-H alkylation using nitroalkanes as the alkyl source. A quaternary ammonium salt derived from quinine containing a sterically hindered urea at the C-9 position was found to effect atroposelective C(sp2)-H alkylation with moderate to good enantioselectivities across several naphthoquinone-containing diaryl ethers. Products can then be isolated in greater than 95:5 er after one rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 36 publications
(49 reference statements)
0
20
0
Order By: Relevance
“…Solvent screening revealed that the reaction went smoothly in various solvents, but 1,4-dioxane was the best choice (entries [8][9][10][11][12]. Evaluation of the bases showed that weak organic and inorganic bases did not work for this reaction, while DBU and K 2 CO 3 led to much better enantioselectivity with slightly reduced yields (entries [13][14][15][16]. Improvement of the yield with excellent enantioselectivity was achieved for the reaction with 15 mol % loading of preNHC E (entries 17 vs [18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Solvent screening revealed that the reaction went smoothly in various solvents, but 1,4-dioxane was the best choice (entries [8][9][10][11][12]. Evaluation of the bases showed that weak organic and inorganic bases did not work for this reaction, while DBU and K 2 CO 3 led to much better enantioselectivity with slightly reduced yields (entries [13][14][15][16]. Improvement of the yield with excellent enantioselectivity was achieved for the reaction with 15 mol % loading of preNHC E (entries 17 vs [18][19].…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, Gustafson and colleagues published an atroposelective synthesis of diaryl ethers via C­(sp 2 )–H methylation with nitromethanes, utilizing quinine-derived quaternary ammonium cations as catalysts (Figure ). The methylation reaction was optimized using substrate 51.1 , along with 10 equiv of NO 2 Me, 10 equiv of K 3 PO 4 , 10 mol % of catalyst 51.2 , and 3 Å molecular sieves (MS) in toluene at room temperature for 24 h, leading to the formation of product 51.3 in 68% yield and 82:18 er, along with a nitroethylated side product 51.4 . The substrate scope was evaluated; however, lower yields and enantioselectivities were observed for substitutions at the ortho position of the phenyl ring other than chloride ( 51.5 – 51.7 ).…”
Section: Dynamic Kinetic Reactions Of Atropisomersmentioning
confidence: 99%
“…Atropisomerism, a form of conformational chirality resulting from hindered rotation about a σ-bond, has been observed in various pharmaceutically relevant scaffolds . Known rotation-restricted σ-bonds in atropisomers include C–X bonds (X = C, N, O, P, S, B) and X–X (X = N) bonds . Acyclic diaryl secondary amines, possessing two potential contiguous atropisomeric C–N axes, represent one of the most privileged scaffolds in biologically active natural products and pharmaceuticals (Scheme a).…”
Section: Introductionmentioning
confidence: 99%